2019
DOI: 10.1016/j.molmet.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

RGS2: A multifunctional signaling hub that balances brown adipose tissue function and differentiation

Abstract: ObjectiveRecruitment of brown adipose tissue (BAT) is a potential new strategy for increasing energy expenditure (EE) to treat obesity. G protein–coupled receptors (GPCRs) represent promising targets to activate BAT, as they are the major regulators of BAT biological function. To identify new regulators of GPCR signaling in BAT, we studied the role of Regulator of G protein Signaling 2 (RGS2) in brown adipocytes and BAT.MethodsWe combined pharmacological and genetic tools to investigate the role of RGS2 in BAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 63 publications
0
16
1
Order By: Relevance
“…In addition, recruitment of inflammatory cells, neutrophils and eosinophils to the bronchoalveolar lavage fluid were significantly increased in RGS2 -/mice (George et al, 2017). Altogether, these data suggest that RGS2 plays a protective against airway hyperreactivity and may be a promising Additional suggested physiological functions for RGS2 include, but are not limited to, kidney fibrosis progression regulation (Jang et al, 2014), brown adipose tissue function and differentiation (Klepac et al, 2019), as well as serving as a key regulator of pancreatic β-cell function (Dong et al, 2017). In a 2017 study, RGS2 -/mice were found to have enhanced β-cell apoptosis and dysregulated insulin secretion in response to glucose challenge.…”
Section: Additional Clinical Implicationsmentioning
confidence: 85%
“…In addition, recruitment of inflammatory cells, neutrophils and eosinophils to the bronchoalveolar lavage fluid were significantly increased in RGS2 -/mice (George et al, 2017). Altogether, these data suggest that RGS2 plays a protective against airway hyperreactivity and may be a promising Additional suggested physiological functions for RGS2 include, but are not limited to, kidney fibrosis progression regulation (Jang et al, 2014), brown adipose tissue function and differentiation (Klepac et al, 2019), as well as serving as a key regulator of pancreatic β-cell function (Dong et al, 2017). In a 2017 study, RGS2 -/mice were found to have enhanced β-cell apoptosis and dysregulated insulin secretion in response to glucose challenge.…”
Section: Additional Clinical Implicationsmentioning
confidence: 85%
“…Regulator of G-protein signaling (RGS) proteins terminate G-protein signaling by accelerating GTPase activity of heterotrimeric Gα-subunits [ 7 ]. RGS2 is one of the most widely studied proteins of the RGS family and preferentially inhibits signaling mediated by heterotrimeric G q/11 proteins [ 8 , 9 ] and has been associated with critical physiological processes such as regulation of blood pressure, cardiac remodeling, and immune responses [ 10 ]. As a critical regulator of G protein-coupled receptor (GPCR) signaling, its deficiency or low expression under experimental or pathological conditions severely affects important physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As a critical regulator of G protein-coupled receptor (GPCR) signaling, its deficiency or low expression under experimental or pathological conditions severely affects important physiological conditions. RGS2 deficiency, for example, accelerates the progression of kidney fibrosis [ 11 ], enhances β-cell apoptosis and dysregulate insulin secretion in response to a glucose challenge [ 12 ], and promotes severe adipogenesis and lipolysis in brown adipose tissue [ 9 ]. Additionally, RGS2 upregulation attenuates phenylephrine hypertrophic effects via α 1 -adrenergic receptors in cultured ventricular myocytes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 The pathway by which CRTC3 protein may be mediating lipolysis has not been described in detail, but evidence suggests that it is through activation of RGS2 expression. 6,13 In order to evaluate the effective approach to downregulate RGS2 gene expression mediated by CRTC3-siRNA in human adipocytes, the aims of this study were to synthesize SiO 2 NPs, to characterize their morphological properties, to evaluate their cytotoxicity effect, and to assess their intracellular localization and capability to deliver siRNA to cultured cells to downregulate RGS2 gene expression. This study evaluates the potential that SiO 2 NPs conjugated with CRTC3-siRNA have to function as a delivery vehicle in an in vitro model to downregulate RGS2 expression levels in HPAd.…”
Section: Introductionmentioning
confidence: 99%